2019
DOI: 10.3390/f10080629
|View full text |Cite
|
Sign up to set email alerts
|

Prolonging Rotation of Chinese Fir to over 25 Years Could Maintain a Better Soil Status in Subtropical China

Abstract: Although Chinese fir (Cunninghamia lanceolata (Lamb.) Hook) is an important species for wood production in subtropical China, it serious declines in soil nutrients and timber productivity in plantations have been reported, probably caused by successive rotation and inappropriate cutting time. Although the significant effect of stand age on soil properties has been widely recognized, research on soil enzymes and microbial communities is relatively rare. In this study, assuming that short rotation period is one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…including Cytophaga and Flexibacter [23]. Overall, our results indicate that microbial biomass and specific groups, as important indicators of soil microbial communities [24,25], were dependent on the extraction methods. Care should be taken when using ELFA to estimate microbial biomass and composition in soils where living organisms may not account for the majority of extracted fatty acids.…”
Section: Plos Onementioning
confidence: 68%
“…including Cytophaga and Flexibacter [23]. Overall, our results indicate that microbial biomass and specific groups, as important indicators of soil microbial communities [24,25], were dependent on the extraction methods. Care should be taken when using ELFA to estimate microbial biomass and composition in soils where living organisms may not account for the majority of extracted fatty acids.…”
Section: Plos Onementioning
confidence: 68%
“…The vegetation characteristics mainly include aboveground vegetation species (Pickles et al, 2015;Toju et al, 2018), species richness and diversity of vegetation (Chen et al, 2017;Francioli et al, 2020), and stand age (Miao et al, 2019;Guo et al, 2020b). In the early stage, revegetation substantially improves the physiological activities of soil fungi and changes the fungal community structure (Liu et al, 2019a;Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Chinese fir ( Cunninghamia lanceolata ) is a subtropical, fast-growing timber species with the largest plantation area of artificial forests in China. However, due to successive rotation, these forests face a number of management problems including declines in productivity, soil fertility ( Miao et al, 2019 ), and biodiversity ( Xu et al, 2020 ). Previous studies have shown that these declines might be related to the low soil nutrient availability ( Ma et al, 2007 ; Wu et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%